Examining the Role of Parental Involvement, School Facilities, Teacher Innovation, and Learning Environment on Student Learning Outcomes - Reky Lidiana Banu (Malaqbi Publisher, 2026)
This study examines the role of parental involvement, school facilities, teacher innovation, and learning environment in influencing student learning outcomes. Using a quantitative research approach with an explanatory design, data were collected from 250 secondary school students through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that all variables—parental involvement, school facilities, teacher innovation, and learning environment—have a positive and significant effect on student learning outcomes. Among these factors, teacher innovation and learning environment were found to have the strongest influence, highlighting the critical role of effective teaching practices and a supportive educational atmosphere. The model demonstrates strong explanatory power, with 68.2% of the variance in student learning outcomes explained by the independent variables. These findings suggest that improving student performance requires a holistic approach that integrates family engagement, adequate school infrastructure, innovative teaching strategies, and a conducive learning environment. This study provides practical implications for educators, policymakers, and school administrators in designing strategies to enhance educational quality and student achievement.